2021
DOI: 10.1177/1534734620986679
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Clinical Profile and Management of Cellulitis of Lower Limb in Northern India

Abstract: Cellulitis is a bacterial infection of the dermis and subcutaneous tissues occupying a large proportion of hospital beds. This study was conducted for analysis of patients with cellulitis according to their demographics and clinical presentation and to examine their comorbidities, complications, and its management. This observational cross-sectional study was conducted in the Department of Surgery at Santosh Medical College and Hospitals involving a total of 60 cases having cellulitis and other soft tissue inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Cellulitis is fairly common and is usually treated in outpatient settings [ 25 ]; however, our study is in that our analysis comprised only cellulitis patients admitted to general surgical in-hospital care. In our analysis, the mean hospital stay was four days, whereas a study from northern India reported a mean hospital stay of 5.02 days [ 22 ]. For the most part, data on demographics, disease characteristics, in-hospital course, and outcomes reveal trends similar to those of non-Hajj cohorts [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Cellulitis is fairly common and is usually treated in outpatient settings [ 25 ]; however, our study is in that our analysis comprised only cellulitis patients admitted to general surgical in-hospital care. In our analysis, the mean hospital stay was four days, whereas a study from northern India reported a mean hospital stay of 5.02 days [ 22 ]. For the most part, data on demographics, disease characteristics, in-hospital course, and outcomes reveal trends similar to those of non-Hajj cohorts [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 73%
“…In our case, the non-white ethnic bias as well as the broad ethnic make-up within each nationality precluded such an investigation. However, a recent analysis from northern India found the leg to be the most common site affected [ 22 ]. Our results, nonetheless, show a patient’s nationality, in part, mirroring that of the general pilgrim population.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [ 13 , 14 ] cellulitis complications were more commonly observed in male patients. This was also identified in our study with a P-value of 0.047.…”
Section: Discussionmentioning
confidence: 89%
“…Infectious organisms are identified in about 15% of cases; most of them are β-hemolytic Streptococcus and Staphylococcus aureus [ 9 ]. The infection can occur anywhere on the body, and the lower extremities are affected in most cases [ 13 ]. Cellulitis is usually thought to be caused by β-hemolytic Streptococcus and Staphylococcus aureus, and the presence of β-hemolytic Streptococcus and/or Staphylococcus aureus in the toe webs was strongly considered as a risk factor for cellulitis.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulitis is usually thought to be caused by β-hemolytic Streptococcus and Staphylococcus aureus, and the presence of β-hemolytic Streptococcus and/or Staphylococcus aureus in the toe webs was strongly considered as a risk factor for cellulitis. Other risk factors associated with cellulitis include trauma, diabetes, smoking, chronic venous insufficiency, edema, destroyed skin barrier, previous history of bacterial cellulitis, existence of erosions or ulcers of the lower extremities, and a history of saphenectomy [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%